Immunohistochemical Expression of Vascular Endothelial Growth Factor (VEGF) in Primary Canine Mast Cell Tumors and Related Regional Lymph Node Metastasis - Alice Corrêa Rassele; Isabella Oliveira Almeida; Maylla Garschagen Gava; Pedro Antônio Bronhara Pimentel; Antonio Giuliano; Felipe Augusto Ruiz Sueiro; Ayisa Rodrigues de Oliveira; Andrigo Barboza de Nardi; Rodrigo dos Santos Horta (Animals)
Vascular endothelial growth factor (VEGF) is an important regulator of angiogenesis and has been identified as an autocrine growth factor for neoplastic cells of several tumors. The aim of this study was to evaluate VEGF expression in canine mast cell tumors and their respective lymph node metastases. For this purpose, 28 patients with mast cell tumors and confirmed regional lymph node metastasis were selected. The samples were submitted for analysis with immunohistochemistry. VEGF was expressed in 14/28 patients (50%) and 35.7% of primary MCTs (10/28), and only 14.3% expressed VEGF in both the primary tumor and its respective metastasis (4/28), with fair agreement (Κ = 0.250). There was a weak correlation between VEGF and tumor size (p = 0.016, rs = 0.045). In this cohort, survival time was correlated with Kiupel grade, mitotic index, tumor necrosis, tumor location, and systemic treatment. VEGF immunolabeling had no influence on survival; however, patients with positive expression may benefit from specific therapy.